1996
DOI: 10.1097/00006454-199612000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole vs. Amphotericin B for the Treatment of Neonatal Fungal Septicemia: A Prospective Randomized Trial

Abstract: Fluconazole showed fewer side effects than amphotericin B and was more convenient to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(66 citation statements)
references
References 16 publications
1
62
0
3
Order By: Relevance
“…In contrast to the percentage of resistant isolates observed in 1992 to 2001 for isolates from this age group (7%) (63), 27% of the current isolates were resistant to fluconazole. This increased resistance may reflect the increased use of fluconazole prophylaxis and treatment in these groups of younger patients (12,27,49,57,58). Whereas the proportion of BSI isolates of Candida that were C. glabrata increased with patient age, the rate of fluconazole resistance declined (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the percentage of resistant isolates observed in 1992 to 2001 for isolates from this age group (7%) (63), 27% of the current isolates were resistant to fluconazole. This increased resistance may reflect the increased use of fluconazole prophylaxis and treatment in these groups of younger patients (12,27,49,57,58). Whereas the proportion of BSI isolates of Candida that were C. glabrata increased with patient age, the rate of fluconazole resistance declined (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies support the use of fluconazole as preferred therapy in the treatment of systemic infections caused by Candida albicans [5,19,20,21]. In cases of poorly susceptible Candida species like C. krusei or C. glabrata, amphotericin B is the drug of first choice.…”
Section: Discussionmentioning
confidence: 99%
“…The only randomised controlled trial (RCT) comparing azoles to amphotericin B for the treatment of IC in children is a trial of 23 neonates with candidaemia. 47 Patients were randomised to receive AmB-D 1 mg/kg/day or fluconazole 5 mg/kg/day, with no reported difference in outcomes. A 2010 Cochrane review of the treatment of suspected (prolonged fever and neutropenia) and proven IC identified four RCTs comparing AmB-D with lipid formulations of amphotericin and one trial comparing itraconazole with fluconazole for candidaemia.…”
Section: Treatment Of Invasive Candidiasis and Candidaemiamentioning
confidence: 99%